Taxonomic Notes on Passiflora edulis var. flavicarpa Deg. - Bidyut Phukon; Chayanika Bordoloi (International Journal of Agriculture System, 2020)
The taxonomic study of a plant is an important aspect of plant research, as it allows the most complete view of the natural habitat of any plant species. The main purpose of the present work is to provide a detail investigation of the Passiflora edulis var. flavicarpa Deg. carried out from the month of April, 2020, growing in the area of Nakachari, Jorhat District, Assam, India. A complete workout on the different parts of the plant belongs to the family Passifloraceae is done to understand the significance of these features in systematic. Paper also reflects the various phytochemical constituents present in the Passiflora fruit also commonly known as Passion fruit which is utilized in pharmacology and by other ways in different ethnic groups of North Eastern India as a vital source of medicinal treatment. The findings clearly express that Passiflora species exhibits all advanced morphological characteristics of present day Angiospermae land plants and also reported that tendrils perform the role of physical support. Towards the end the study it is also concludes with the beneficial outputs of Passiflora edulis from the agronomical point of view that can be easily achievable if the input through cultivation would be uniform as well as dynamic. Based on the various literature surveys, it was found that such detail taxonomic works on the species were not studied and recorded from the study area earlier. Such comprehensive work on Passiflora edulis var. flavicarpa provides an empirical basis for the identification of the species.